Construction workspace management: critical review and roadmap. Issue 10 (27th July 2022) - Igwe, Charles; Nasiri, Fuzhan; Hammad, Amin
Abstract: Construction workspace management has been a big issue in research and practice in recent years due to the need to improve productivity and safety by reducing spatio-temporal clashes in the management of construction projects. The complexities and dynamic nature of construction sites make construction workspace management difficult due to the continually evolving nature of the workspace. The space planning problem in construction has two main elements that are interdependent but require different approaches: the space scheduling problem, focused on the planning of task execution spaces, and the site layout problem, focused on the location of temporary facilities of various kinds. However, despite the importance of construction workspace management, a comprehensive review of the subject matter is absent in the literature. The objectives of this study are (1) to identify prominent themes in published research; (2) to compare work published within each theme; and (3) to suggest future directions for construction equipment space planning.